Facile Generation of L10‐FePt Nanodot Arrays from a Nanopatterned Metallopolymer Blend of Iron and Platinum Homopolymers. (17th September 2013) - Dong, Qingchen; Li, Guijun; Ho, Cheuk‐Lam; Leung, Chi‐Wah; Pong, Philip Wing‐Tat; Manners, Ian; Wong, Wai‐Yeung
<x xml:space="preserve">Abstract</x> Hard ferromagnetic (L10 phase) FePt alloy nanoparticles (NPs) with extremely high magnetocrystalline anisotropy are considered to be one of the most promising candidates for the next generation of ultrahigh‐density data storage system. The question of how to generate ordered patterns of L10‐FePt NPs and how to transform the technology for practical applications represents a key current challenge. Here the direct synthesis of L10 phase FePt NPs by pyrolysis of Fe‐containing and Pt‐containing metallopolymer blend without post‐annealing treatment is reported. Rapid single‐step fabrication of large‐area nanodot arrays (periodicity of 500 nm) of L10‐ordered FePt NPs can also be achieved by employing the metallopolymer blend, which possesses excellent solubility in most organic solvents and good solution processability, as the precursor through nanoimprint lithography (NIL). Magnetic force microscopy (MFM) imaging of the nanodot pattern indicates that the patterned L10 phase FePt NPs are capable of exhibiting decent magnetic response, which suggests a great potential to be utilized directly in the fabrication of bit patterned media (BPM) for the next generation of magnetic recording technology.